Temperature dependence of the transport of single‐file water molecules through a hydrophobic channel. Issue 12 (17th January 2016) - Su, Jiaye; Yang, Keda
Abstract : Although great effort has been made on the transport properties of water molecules through nanometer channels, our understanding on the effect of some basic parameters are still rather poor. In this article, we use molecular dynamics simulations to study the temperature effect on the transport of single‐file water molecules through a hydrophobic channel. Of particular interest is that the water flow and average translocation time both exhibit exponential relations with the temperature. Based on the continuous‐time random‐walk model and Arrhenius equation, we explore some new physical insights on these exponential behaviors. With the increase of temperature, the water dipoles flip more frequently, since the estimated flipping barrier is less than 2 k B T . Specifically, the flipping frequency also shows an exponential relation with the temperature. Furthermore, the water‐water interaction and water occupancy demonstrate linear relations with the temperature, and the water density profiles along the channel axis can be slightly affected by the temperature. These results not only enhance our knowledge about the temperature effect on the single‐file water transport, but also have potential implications for the design of controllable nanofluidic machines. © 2016 Wiley Periodicals, Inc. Abstract : Molecular dynamics simulations were used to study the temperature effect on the transport of single‐file water molecules through a hydrophobic channel. Of particular interest is that the water flow and average translocation time both exhibit exponential relations with temperature.